Agama, Konflik dan Integrasi Sosial Refleksi Kehidupan Beragama di Indonesia: Belajar dari Komunitas Situbondo Membangun Integrasi Pasca Konflik - Retnowati, Pdt (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2018)
The research discusses the settlement effort and reconciliation postriot in Situbondo, East Java. The settlement effort and reconciliation have been carried out by community in Situbondo, especially Islamic and Christian Community to build integration in Situbondo community. To get the data on the role of religious community in this case Islam and Christian as well as the community in Situbondo in general, is got through interview, survey initiated by light observation before doing research. The secondary data is got through review of literature relevant to research problems. Conflict theory, social integration, and re conciliation are used to explain and analyze research problems based on the data gathered. The finding shows that the integration in Situbondocommunity and reconciliation effort have been carried out by religious community, Islam, Christian and the whole community of Situbondo. The local wisdom of community in Situbondo serves as social capital in manifesting integration in the community so in the post conflict the life of Situbondo community and the relation between religious community in Situbondo experienced the inconveniences can harmonious again.